1987
DOI: 10.1111/j.1471-4159.1987.tb02894.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle‐Specific Requirement for Mevalonate, but Not for Cholesterol, for DNA Synthesis in Glial Primary Cultures

Abstract: The requirement for the sterol biosynthetic pathway for the occurrence of DNA synthesis in glial cells and, in particular, the relative roles of cholesterol and of mevalonate have been studied. Primary cultures of developing glial cells were synchronized by reducing the content of fetal calf serum (FCS) in the culture medium from 10% to 0.1% (vol/vol) for 48 h between days 4 and 6 in culture. Reversal of the resulting quiescent state by the return of the cultures to 10% serum caused after 24 h a marked increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 60 publications
3
44
1
Order By: Relevance
“…A recent study has shown that statins cause intracellular accumulation of A␤ via a non-steroidal isoprenoid-dependent mechanism (67). In our study, however, we added mevalonate to avoid toxicity due to inhibition of these non-steroidal pathways (51,52,54).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study has shown that statins cause intracellular accumulation of A␤ via a non-steroidal isoprenoid-dependent mechanism (67). In our study, however, we added mevalonate to avoid toxicity due to inhibition of these non-steroidal pathways (51,52,54).…”
Section: Discussionmentioning
confidence: 96%
“…De novo cholesterol synthesis was inhibited by lovastatin, an inhibitor of HMG-CoA reductase. A basic level of mevalonate was maintained by adding mevalonate to the cell culture media to avoid toxicity due to inhibition of non-steroidal pathways (51,52). Plasma membrane cholesterol was extracted by methyl-␤-cyclodextrin.…”
Section: Methodsmentioning
confidence: 99%
“…First, de novo synthesis of cholesterol was inhibited by lovastatin or simvastatin. Biochemical pathways for nonsteroidal products were allowed to proceed by supplementing cells with mevalonate in the culture medium (33,34). Second, plasma membrane cholesterol was extracted by CDX, which is very efficient in selectively and rapidly extracting cholesterol from the plasma membrane (35).…”
Section: Resultsmentioning
confidence: 99%
“…Lovastatin and simvastatin are known to reversibly arrest the cell cycle progression of mammalian cells in the G, phase with drug concentrations ranging from 1 to 10 pug -ml -for human bladder carcinoma T24 cells (11) and human fibroblasts (15) to 60 ,ug -ml-1 for rat brain glial cells (14). Blocked cells are viable, and cytostatic effects can be reversed by the addition of exogenous mevalonate, the product of the HMG-CoA reductase reaction.…”
Section: Discussionmentioning
confidence: 99%
“…After the 30th hour, corresponding to the beginning of the schizont stage, the inhibition of growth was weak or totally absent. Lovastatin and simvastatin are known to act as competitive inhibitors of HMG-CoA reductase and to block the proliferation of eukaryotic cells in the GI phase (11,14,15). For example, treated human bladder carcinoma T24 cells are viable for up to 72 h and are able to enter into the S phase after removal of the drug (11).…”
Section: Methodsmentioning
confidence: 99%